Hyperkinetic movement disorders - Suchowersky, Oksana (Current clinical neurology)
Hyperkinetic Movement Disorders is a state-of-the-art resource devoted to disorders characterized by excessive movement.  Organized according to specific disorders or syndromes, each chapter is written by a group of internationally recognized experts. Chapters have been organized by the individual authors to best highlight the salient features of the disorders.  Each chapter features a video accompaniment that provides highly instructive examples of each disorder, offering clinicians an important video-based tool to aid in making correct diagnoses.  The video is on an accompanying DVD and can also be found at www.springerimages.com/Suchowersky.  Without a visual evaluation of the phenomenology, diagnosis of the hyperkinetic disorder is fraught with error.  Hyperkinetic Movement Disorders is a unique and essential new text written for neurologists, psychiatrists, neurosurgeons, internists, residents and all others interested in movement disorders.  An invaluable resource, it will lead to a better understanding and recognition of the hyperkinetic movement disorders, and that, in turn, will lead to better care for patients. Pathophysiology of hyperkinetic movement disorders - Huntington disease and other choreas - Dystonia - Tourette syndrome and the spectrum of neurodevelopmental tic disorders - Myoclonus - Paroxysmal dyskinesias - Psychogenic movement disorders - Drug-induced hyperkinetic movement disorders - Hyperkinetic disorders in childhood - Surgery for hyperkinetic movement disorders.